Media, Technology Use, and Attitudes: Associations With Physical and Mental Well‐Being in Youth With Implications for Evidence‐Based Practice. Issue 4 (15th May 2018) - Zeeni, Nadine; Doumit, Rita; Abi Kharma, Joelle; Sanchez‐Ruiz, Maria‐Jose
ABSTRACT: Background: Previous research has shown that the use of technology and media, in their different available forms, may have detrimental effects on the physical and mental well‐being of adolescents and young adults. Aims: The present study aimed to investigate the use of different types of technology and media, attitudes toward them, and how they relate to physical and mental well‐being in Lebanese university students. Methods: A descriptive, correlational, cross‐sectional design was used. A sample of 244 undergraduates completed a self‐report measuring media and technology use and attitudes, eating‐related variables (e.g., healthy eating, body image dissatisfaction [BID], and eating disorders [EDs] risk), trait emotional intelligence (TEI), and psychopathology indicators (stress, anxiety, and depression). Results: The use of mobile phone multimedia (music, pictures, and videos) correlated with unhealthy eating and stress. Social media use was associated with BID, EDs risk, and the self‐control construct of TEI. Anxiety of separation from technological devices and dependence on them was associated with increased BID, EDs risk, depression, and anxiety. Linking Evidence to Action: Practical implications are discussed in terms of setting limits and boundaries on technology use during childhood and adolescence, and encouraging healthy eating and physical activity at home and on college campuses. Moreover, social media could be used as a platform for intervention and prevention programs to decrease BID, EDs, depression, and anxiety.